The temple complex at Horvat Omrit - Overman, J. Andrew 1955-; Schowalter, Daniel N. 1957-; Nelson, Michael C. 1965- (Leiden Brill, 2015)
"Volume One of The Temple Complex at Horvat Omrit presents a detailed examination of the surviving architecture of the three Roman period temple phases at the newly excavated sanctuary at the archaeological site of Omrit in northern Israel. All three temples were built according to the Corinthian order and the author describes and illustrates the state of the remains, proposes reconstructions of each phase, and places each temple in the broader historical context"--Provided by publisher.
Volume 1 The architecture by M.C. Nelson
Includes bibliographical references and index.
Keywords: Omrit Site (Israel); Temples, Roman -- Israel; Excavations (Archaeology) -- Israel; 902 <569.4> -- Archeologie--Israël; Israel -- Antiquities